Common Variants in the ATP-binding Cassette Transporter 1 Gene with Decreased HDL-Cholesterol Levels and Coronary Artery Disease - (:unkn) unknown (ELSEVIER SCIENCE INC, 2008)
Background. Our aim was to determine whether the common variants within the coding sequence of ABCA1 gene affects low plasma high-density lipoprotein cholesterol (HDL-C) levels in Turkish patients with coronary artery disease (CAD). The study group was composed of 552 CAD patients, of which 251 had HDL-C levels <= 40 mg/dL, and 301 had HDL-C levels > 40 mg/dL. Methods. PCR-RFLP was used to determine the A2589G and G3456C DNA polymorphisms of the ABCA1 gene. The study group was analyzed for potential clinical predictors of low HDL-C. Results. The GG variant of the ABCA1 gene A2589G polymorphism was found in 3.6% patients within the HDL-C <= 40 mg/dL group and in 4% of HDL-C levels >40 mg/dL group. Frequency distributions of the A2589G genotypes were not found to differ significantly among groups. The CC genotype of the G3456C polymorphism was found in 6.8% of HDL-C <= 40 mg/dL group and in 11.6% individuals of the HDL-C levels >40 mg/dL group. Frequency distributions of the G3456G genotypes were not significantly different among groups. The A2589G genotypes were not found to be effective over the analyzed lipid parameters. Among G3456C genotypes, in CAD patients with HDL-C <= 40 mg/dL the low-density lipoprotein (LDL-C) levels were elevated, whereas HDL-C levels decreased in CC genotype carriers compared to GG and GC. Conclusions. No significant association was found between cardiovascular endpoints and ABCA1 gene A2589G and G3456C genotypes in this study population. (C) 2008 IMSS. Published by Elsevier Inc.
Keywords: Coronary artery disease; Low HDL; G3456; A2589G; Cardiovascular endpoints; DENSITY-LIPOPROTEIN CHOLESTEROL; APOLIPOPROTEIN-A-I; TANGIER-DISEASE; HEART-DISEASE; ABC TRANSPORTERS; DEFICIENCY; LIPIDS; RISK; MEN; MUTATIONS